Review of Prevention Schemes for Man-In-The-Middle (MITM) Attack in Vehicular Ad hoc Networks - Mahmood A. Al-shareeda; Mohammed Anbar; Selvakumar Manickam; Iznan H. Hasbullah (International Journal of Engineering and Management Research, 2020)
Vehicular Ad-Hoc Network (VANET) is an indispensable part of the Intelligent Transportation System (ITS) due to its abilities to enhance traffic management and safety. Many researchers have been focused on specific areas involving management and storage data, protocols standardization, network fragmentation, monitoring, and quality of service. The benchmarks of security of VANET are studied and figured out in this paper. VANET provides the driver and passenger with the safety application as well as entertainment service. However, the communication between nodes in VANET is susceptible to security threats in both communication modes, which indicates the main hazard. In this paper, we identified different Man-In-The-Middle (MITM) attacks with various behaviors such as message tampering, message delaying, and message dropping, according to the literature. In this study, the essential background of VANET from architectural point of view and communication types are discussed. Then, the overview of MITM attack in VANET is presented. In addition, this paper thoroughly reviews the existing prevention schemes for MITM attack in VANET. This review paper reveals that there is still a need for a better and more efficient preventive scheme to address the MITM attack in VANET. This review paper could serve as evidence and reference in the development of any new security schemes for VANETs.